2018
DOI: 10.3390/su10072540
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Obligatory Passage Points to Sustain Service Systems: The Case of Traditional Market Revitalization in Hsinchu City, Taiwan

Abstract: City" could be viewed as an integration of various service systems with relocated social, economic, and environmental capitals under urbanization. It was evidential in Hsinchu City, Taiwan, where once the biggest market, Dongmen Market (DMM), declined because the replacement of urban consumption patterns along with the setup of high tech science park bringing new residences. This research took the perspectives of Service-Dominant Logic (S-DL) and Actor Network Theory (ANT) to study the development of new servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…Parlee and Wiber (2018) discuss innovative conflict resolution to strengthen governance in the context of the Canadian marine environment. Other SOI studies have also been conducted in the contexts of community (Lynch et al , 2017), public organisations (Mallett and Cherniak, 2018) and regional management (Chen and Lin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Parlee and Wiber (2018) discuss innovative conflict resolution to strengthen governance in the context of the Canadian marine environment. Other SOI studies have also been conducted in the contexts of community (Lynch et al , 2017), public organisations (Mallett and Cherniak, 2018) and regional management (Chen and Lin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the urban sustainability issues have become more complex, including global warming, climate change and social inequality and therefore, the SOI increasingly calls for practical enlargements, from only business sectors to public and non-profit organisations (Martiskainen, 2017; Stephens and Jiusto, 2010). This is followed by a significant conceptual development of SOI, which adopts new contexts such as sustainable community (Lynch et al , 2017), public organisations (Mallett and Cherniak, 2018) and regional management (Chen and Lin, 2018). The concept of SOI is arguably more complex, whilst its theoretical-empirical development is still limited and thus, literature development is required (Harsanto and Permana, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Velly and Dufeu [16] applied actor-network theory to analyze the "alternative local food network" as well as the multiple interconnections between local market devices and market mediation in order to establish a regular alternative local food network system. Chen and Lin [23] applied actor-network theory to study the development of new city service systems through interventions and the method of system analysis based on actor-network theory will be applied to describe the long-term system development rather than cross-sectional snapshots.…”
Section: Actor-network Theorymentioning
confidence: 99%
“…Researchers link these feelings and the value pursued by consumers to effectively demonstrate consumers' real experiential value. The results of previous studies have shown an excellent effect on the performance of system analysis, for example, Chen and Lin [23] suggested that further studies could demonstrate the system formation and actors' interaction in a structural way. Although Penghu, located on an outlying island of Taiwan, is rich in marine and aquatic products as well as unique local agricultural products, the unstable demand and supply have often led to stagnation in sales.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research on the formation and dynamics of the system for social innovation (Babu et al, 2020;Chen and Lin, 2018;Polese et al, 2018) have highlighted key activities by network actors such as searching for collaborators, searching for opportunities for the innovation, implementing bilateral and multilateral resource integration in the network, and convincing others of the benefits of the social innovation. These activities strongly involve the interaction of humans.…”
Section: Introductionmentioning
confidence: 99%